Chronic oral fistula and bladder stones management in a sulcata tortoise (Centrochelys sulcata) - Wibowo, Deny Setyo; Esfandiari, Anita; Iman, Bintang Nurul; Rahmiati, Dwi Utari; Fitri, Arni Diana (ARSHI Veterinary Letters, 2024)
This case study aimed to illustrate the clinical management and therapeutic strategies required for a 4-year-old male Sulcata tortoise named Swift, who presented with significant health issues, including an oral fistula and bladder stones, often indicative of broader husbandry problems. Swift weighed 13 kg and exhibited symptoms such as extensive white lesions across his mouth, an uneven mouth surface, and a foul odour, along with severe lethargy, refusal to eat or drink, and a drooping head. Physical examination revealed dehydration characterised by sunken eyes and reduced skin turgor. Radiographic findings indicated a mass with increased opacity in the mid-body cavity, suggesting the presence of a bladder stone. The treatment involved anaesthesia with ketamine and midazolam, followed by isoflurane gas for maintenance. Surgical interventions included cleaning the oral cavity, inserting a feeding tube, and removing the bladder stone via a transplastron-celiotomy approach. Postoperative care consisted of intracoelomic administration of antibiotics, vitamins, analgesics, and fluid therapy